COMPREHENSIVE ASSESSMENT OF THE ORAL CAVITY CONDITION IN PRESCHOOL CHILDREN WITH ARTIFICIAL FEEDING - Safarova Mashxura Sulaymonovna (Scholar Express Journal, 2021)
Breastfeeding is one of the most natural and important functions inherent in a woman by nature. All the nutrients of breast milk correspond to the peculiarities of the digestive system and metabolism, the functional capabilities of the gastrointestinal tract of the child, providing him with adequate development. Breast milk is a unique balanced food product that determines the optimal physical and neuropsychic development of children [1.2.4.6.8.12.14]. It has undeniable advantages over other foods for children, because it contains not only nutrients, but also hormones, growth and protective factors, meets the needs of the child.
Keywords: Artificial Feeding; pregnant women; protective factors; system